Preparative high-speed counter-current chromatography separation of grape seed proanthocyanidins according to degree of polymerization. (15th March 2017) - Zhang, Shuting; Li, Lingxi; Cui, Yan; Luo, Lanxin; Li, Yuanyuan; Zhou, Peiyu; Sun, Baoshan
Highlights: HSCCC method was developed to isolate proanthocyanidins in order of polymerization degrees. Seventeen individual proanthocyanidins were obtained with dimers and trimers. The positive correlation was revealed between DP and in vitro antioxidant activities. Abstract: Separation of plant proanthocyanidins remains a major challenge for scientists due to the structural diversity and complexity. In this work, a new and effective method was developed for preparative separation of grape seed proanthocyanidins (GSPs) according to degree of polymerization (DP) by high-speed counter-current chromatography (HSCCC). Under the optimized HSCCC conditions, GSPs could be separated into seven distinct fractions (F1–F7) with mean degree of polymerization in increasing order, from 1.44 to 6.95. High yields for these fractions (53.7, 12.2, 29.5, 30.2, 11.2, 50.8 and 169.8 mg, respectively) were achieved by only one-step HSCCC of 400 mg of GSPs. Further, seventeen individual proanthocyanidins, most of which are commercially not available, were efficiently isolated by re-chromatography on HSCCC or prep-HPLC; each of the isolated compounds presented high yields (7.1–78.9 mg) and high purity (70.0–95.7%). The positive correlation was observed between DP and antioxidant activity of proanthocyanidins.